Large-scale implementation of disease control programmes: a cost-effectiveness analysis of long-lasting insecticide-treated bed net distribution channels in a malaria-endemic area of western Kenya—a study protocol. Issue 11 (21st November 2016) - Gama, Elvis; Were, Vincent; Ouma, Peter; Desai, Meghna; Niessen, Louis; Buff, Ann M; Kariuki, Simon
Abstract : Introduction: Historically, Kenya has used various distribution models for long-lasting insecticide-treated bed nets (LLINs) with variable results in population coverage. The models presently vary widely in scale, target population and strategy. There is limited information to determine the best combination of distribution models, which will lead to sustained high coverage and are operationally efficient and cost-effective. Standardised cost information is needed in combination with programme effectiveness estimates to judge the efficiency of LLIN distribution models and options for improvement in implementing malaria control programmes. The study aims to address the information gap, estimating distribution cost and the effectiveness of different LLIN distribution models, and comparing them in an economic evaluation. Methods and analysis: Evaluation of cost and coverage will be determined for 5 different distribution models in Busia County, an area of perennial malaria transmission in western Kenya. Cost data will be collected retrospectively from health facilities, the Ministry of Health, donors and distributors. Programme-effectiveness data, defined as the number of people with access to an LLIN per 1000 population, will be collected through triangulation of data from a nationally representative, cross-sectional malaria survey, a cross-sectional survey administered to a subsample of beneficiaries in Busia County and LLIN distributors' records. Descriptive statistics and regression analysis will be used for the evaluation. A cost-effectiveness analysis will be performed from a health-systems perspective, and cost-effectiveness ratios will be calculated using bootstrapping techniques. Ethics and dissemination: The study has been evaluated and approved by Kenya Medical Research Institute, Scientific and Ethical Review Unit (SERU number 2997). All participants will provide written informed consent. The findings of this economic evaluation will be disseminated through peer-reviewed publications.